2023
DOI: 10.3390/healthcare11060884
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Video Laryngoscopes and Direct Laryngoscopy for Emergency Endotracheal Intubation While Wearing PPE-AGP: A Randomized, Crossover, Simulation Trial

Abstract: Background: The COVID-19 pandemic has necessitated changes in the safety protocols of endotracheal intubation at every level of care. This study aimed to compare the first-pass success rates (FPS) and intubation times (IT) of three video laryngoscopes (VL) and direct laryngoscopy (DL) for simulated COVID-19 patient emergency intubation (EI). Methods: The study was a prospective, randomized, crossover trial. Fifty-three active paramedics performed endotracheal intubation with the I-viewTM VL, UESCOPE® VL, ProVu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Recent studies on the DL vs. VL technique among novice users have presented inconsistent findings on the superiority of one technique over the other, but improved time metrics and glottic visualization with VLs have been observed, especially in the difficult airway scenario, which is in concordance with our study. Our findings also support previously described similar success rates of the two techniques and the questionable advantage of non-channeled devices for novice operators [ 43 , 44 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recent studies on the DL vs. VL technique among novice users have presented inconsistent findings on the superiority of one technique over the other, but improved time metrics and glottic visualization with VLs have been observed, especially in the difficult airway scenario, which is in concordance with our study. Our findings also support previously described similar success rates of the two techniques and the questionable advantage of non-channeled devices for novice operators [ 43 , 44 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 92%
“…The study of Kluj. et al compared three non-channeled VLs and the Macintosh DL in a simulated environment where PPE-wearing novice users had to execute the intubation, and they could not prove that VLs presented a significant advantage regarding first pass success rates and intubation times [ 43 ]. A recent study of Muhamed et al—evaluating a similar number of novices as our study—found that the evaluated VL performed better in terms of time-related metrics, glottic visualization, and incidence of dental injury, but it showed similar results when it came to success rates and ease of use [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the coronavirus disease-19 (COVID-19) pandemic, more studies have evaluated laryngoscopes because the necessity of wearing personal protective equipment (PPE) for aerosolgenerating procedures has resulted in a change in ETI protocols for safety [31,39]. PPE plays an important role in preventing the spread of disease, however, previous studies suggested that PPE may reduce the effectiveness of ETI [31,40].…”
Section: Comparison Of Endotracheal Intubation Methods: Video Laryngo...mentioning
confidence: 99%
“…[148,149]. It is also noticed that the tracheal intubation procedure might be hampered by the personal protective equipment [150][151][152][153].…”
Section: Covid-19 Pandemicmentioning
confidence: 99%